2008
DOI: 10.1007/s10551-008-9894-x
|View full text |Cite
|
Sign up to set email alerts
|

The Worth of Values – A Literature Review on the Relation Between Corporate Social and Financial Performance

Abstract: One of the older questions in the debate about Corporate Social Responsibility (CSR) is whether it is worthwhile for organizations to pay attention to societal demands. This debate was emotionally, normatively, and ideologically loaded. Up to the present, this question has been an important trigger for empirical research in CSR. However, the answer to the question has apparently not been found yet, at least that is what many researchers state. This apparent ambivalence in CSR consequences invites a literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
583
3
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 870 publications
(683 citation statements)
references
References 67 publications
25
583
3
25
Order By: Relevance
“…However, the majority of these studies on the relationship between CSR and firm performance document a positive relationship. As noted by Halme and Laurila (2009), and Stuebs and Sun (2009), a recent literature review (Beurden and Gössling, 2008), two meta-analyses (Margolis and Walsh, 2003;Orlitzky et al, 2003), and several recent studies (e.g., Brammer and Millington, 2008) support the positive link. Additionally, most of the studies have reached a common conclusion that CSR behavior contributes to a firm's long-term sustainability and growth (Taneja et al, 2011).…”
Section: Impact Of Csr On Financial Performancementioning
confidence: 83%
“…However, the majority of these studies on the relationship between CSR and firm performance document a positive relationship. As noted by Halme and Laurila (2009), and Stuebs and Sun (2009), a recent literature review (Beurden and Gössling, 2008), two meta-analyses (Margolis and Walsh, 2003;Orlitzky et al, 2003), and several recent studies (e.g., Brammer and Millington, 2008) support the positive link. Additionally, most of the studies have reached a common conclusion that CSR behavior contributes to a firm's long-term sustainability and growth (Taneja et al, 2011).…”
Section: Impact Of Csr On Financial Performancementioning
confidence: 83%
“…The proponents of a positive effect of SD practices on performance and those who argue for a contingent, or even negative, relationship are involved in a heated debate (for reviews on this subject, see Beurden and Gössling 2008;Margolis and Walsh 2003;Orlitzky et al 2003).…”
Section: Sustainable Practices and Performancementioning
confidence: 99%
“…However, in most cases, empirical studies have reported a positive relationship between CSR and performance (Beurden and Gössling 2008;Margolis and Walsh 2003;Orlitzky et al 2003). This positive relationship extends to SMEs, in terms of both environmental actions (Aragon-Correa et al 2008;Dixon-Fowler et al 2013) and social actions (Hammann et al 2009).…”
Section: Sustainable Practices and Performancementioning
confidence: 99%
“…Investigation of this link has been the topic of several research studies in the past. A recent literature review on this topic is provided by Beurden and Gössling (2008). However, the available evidence is inconclusive; there are some studies that have found a positive link (e.g., Waddock and Graves 1997), some have found a negative link (e.g., Konar and Cohen 2001), while others have found no link at all (e.g., Berman et al 1999).…”
Section: Introductionmentioning
confidence: 99%